2007
DOI: 10.1007/s00425-007-0602-3
|View full text |Cite
|
Sign up to set email alerts
|

Potato steroidal glycoalkaloid levels and the expression of key isoprenoid metabolic genes

Abstract: The potato steroidal glycoalkaloids (SGA) are toxic secondary metabolites, and their total content in tubers should not exceed 20 mg/100 g fresh weight. The two major SGA in cultivated potato (Solanum tuberosum) are alpha-chaconine and alpha-solanine. SGA biosynthetic genes and the genetic factors that control their expression have not yet been determined. In the present study, potato genotypes exhibiting different levels of SGA content showed an association between high SGA levels in their leaves and tubers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 51 publications
2
49
0
2
Order By: Relevance
“…Jones and Fenwick, (2006) and Krits et al (2007) suggested that the level of total glycoalkaloids in potato tubers should not exceed 200 mg/kg of fw (or 200 mg/100 g of dw). Although ANOVA showed no significant effect of the rootstock on glycoalkaloids concentration, our results revealed a certain effect of rootstocks on glycoalkaloids content.…”
Section: Discussionmentioning
confidence: 99%
“…Jones and Fenwick, (2006) and Krits et al (2007) suggested that the level of total glycoalkaloids in potato tubers should not exceed 200 mg/kg of fw (or 200 mg/100 g of dw). Although ANOVA showed no significant effect of the rootstock on glycoalkaloids concentration, our results revealed a certain effect of rootstocks on glycoalkaloids content.…”
Section: Discussionmentioning
confidence: 99%
“…In most cultivated potato species, derivatives of 3-O-glucosylsolanidine are more abundant than those of 3-O-galactosylsolanidine (Friedman et al, 2003). Interestingly, several genotypes of Solanum chacoense exhibit higher relative levels of SGT1 (galactosyltransferase) than of SGT2 (glucosyltransferase), suggesting an opposite SA 3-O-glycosylation ratio (galactosylation/glucosylation) (Krits et al, 2007). Enzyme activity assays performed herein, together with previously published data (Zimowski, 1998), support a different mechanism in tomato for regulating the 3-O-glycosylated SA ratio.…”
Section: Game1 Acts Predominantly As a Udp-gal: Tomatidine Galactosylmentioning
confidence: 99%
“…SGAs accumulation appears to be regulated at different steps in the biosynthetic pathway in response to environmental stress and development. High transcript levels of potato HMGR and squalene synthase encoding genes were shown to be associated with high SGA levels (8), implying that the regulation of SGA biosynthesis involves the committed step of the mevalonate pathway as well as later steps of SGA formation. It indicated that along with HMGR, Original Article DOI: 10.5582/ddt.2012.v6.…”
Section: Introductionmentioning
confidence: 99%